2017
DOI: 10.1039/c6ra28405a
|View full text |Cite
|
Sign up to set email alerts
|

The intriguing journey of gH625-dendrimers

Abstract: The knowledge of the mechanism used by vectors to gain access to cell interiors is key to the development\ud of effective drug delivery tools for different pathologies. The role of the initial interaction with the\ud membrane bilayer is widely recognized, although not fully understood. We use neutron reflectivity\ud experiments and internalization studies with cells to reveal the extent of interaction of dendrimers\ud functionalized with the peptide gH625 with biomimetic membranes. We further investigate the\u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
(65 reference statements)
1
6
0
Order By: Relevance
“…We have previously demonstrated a strong correlation between the affinity of gH625 for the lipid bilayer and cellular delivery efficiency, which is consistent with its uptake by a physically mediated process 23 26 ; in fact, to fully describe the biophysical mechanism involved in the molecular mode of action of gH625, the contribution of electrostatic and hydrophobic forces to the process is an essential piece of the puzzle that needs to be elucidated 7 .…”
Section: Introductionsupporting
confidence: 61%
“…We have previously demonstrated a strong correlation between the affinity of gH625 for the lipid bilayer and cellular delivery efficiency, which is consistent with its uptake by a physically mediated process 23 26 ; in fact, to fully describe the biophysical mechanism involved in the molecular mode of action of gH625, the contribution of electrostatic and hydrophobic forces to the process is an essential piece of the puzzle that needs to be elucidated 7 .…”
Section: Introductionsupporting
confidence: 61%
“…The dendrimers, as we have said before, constitute a class of nanoparticles with physicochemical characteristics that make them very attractive in nanomedicine applications, more specifically as drug delivery systems (DDS). As previously mentioned, these extraordinary dendritic macromolecules have an improved membrane permeability and tumor retention effects [87][88][89], due to their suitable structural properties and size control.…”
Section: Dendrimers To Drug Delivery Systems Applicationsmentioning
confidence: 99%
“…The hydrophobicity and amphipathicity are the key features of gH625 that make the peptide interact with membrane lipids and form a transient helical structure to induce membrane organization temporarily. Thereby, it was demonstrated that gH625 is able to cross the cell membrane and to transport many conjugated cargoes into the cytosol (Falanga, Lombardi, et al., 2017; Falanga, Valiante, et al., 2017; Falanga, Galdiero et al., 2018).…”
Section: Cpp Classificationmentioning
confidence: 99%